Features immunologic indicators of chronic tonsillitis associated with Epstein-Barr virus in adults - Kuchma, I; Ovcharenko, S; Kolyada, O; Pochyeva, T; Yampolskya, K (Annals of Mechnikov’s Institute, 2020)
Chronic tonsillitis are the most common diseases of the upper respiratory tract. One of the causes of tonsillitis, with severe clinical manifestations or erased is the Epstein - Barr virus (EBV). According to the literature, more than 90% of the adult population infected with EBV and are lifelong carriers of the virus. After primary infection replication of the virus in asymptomatic or in the case of a weakened immune system may develop infectious mononucleosis. Primary EBV infection in adolescence and adults is much greater than in children and often causes the formation of chronic forms. The main entrance gate is EBV oropharyngeal epithelium. In epithelial cells undergoing complete EBV replication with lysis of cells and the formation of a large number of virions. EBV infects B lymphocytes through the interaction of the surface gp320 virus with CD21 (receptor for complement component C3d). In EBV-infected B lymphocytes are two possible kinds of replication: lytic and latent process. During replication of EBV lytic expressed approximately 100 proteins are immunogenic but are 4 types of proteins, which have specific antibodies: early antigen - EA; viral capsid antigen - VCA; Epstein-Barr nuclear antigen - EBNA; latent membrane protein - LMP. LMP-1 induced bcl-2 (a blocker of apoptosis in B-cells) and promotes proliferation and migration of B-lymphocytes. Thus, EBV infection is characterized by widespread, reactivation of infection from infected parts that most often manifests itself with recurrent infection with symptoms of chronic tonsillitis. Objective: what features of general and local immunological parameters inherent in chronic tonsillitis in the acute stage, caused by reactivation of EBV infection. Materials and methods. The study included 311 patients with chronic tonsillitis subcompensated in the acute stage. Microbiological testing of samples produced from the throat, determined EBV DNA in saliva, EVB-VCA-IgM, EVB-EA-IgG and EVB-NA-IgG in the serum; CBC was performed, the determination of CD3, CD4, CD8, CD16, CD19, IgM, IgG, IgA, IgE, CEC serum cytokines and sIgA in the oropharyngeal fluid. Results and discutions. Group of patients who are not identified in the throat S. pyogenes and S. aureus revealed EBV DNA and identified EVB-EA-IgG and EVB-VCA-IgM was 20 people (chronic tonsillitis associated with EBV infection). A group of patients in whom there was no EBV DNA in saliva and throat was isolated S. pyogenes, S. aureus was 60 people (chronic tonsillitis associated with bacterial infection). Control group consisted of relatively healthy people - 20 people. Patients with EBV infection was observed leukocytosis, lymphocytosis; increasing the number of B lymphocytes (CD19), IgM, IgА and IgE, increasing the CEC, ІNF- Gamma, L-1, IL-4, IL-6, IL-10, IL-17 and sIg A. Patients mentioned bacterial tonsillitis increased Ig G, IgA, and IgE, and a significant increase in CEC; increase ІNF- , IL-1, IL-4, IL-6, IL-17. ІNF-, IL-10 levels were not significantly different from the control. Number sIg A was reduced. Conclusions:1. Relationship between exacerbation of tonsillitis and EBV infection was confirmed by the presence of fluid in the oropharyngeal EBV DNA and antibodies to EBV early antigens. 2. For acute EBV infection is characterized by leukocytosis, lymphocytosis; possibly in the presence of abnormal blood mononuclear cells in a small amount. 3. For acute EBV infection is characterized by increase in the number of B-lymphocytes and levels of IgM, IgА and IgE in serum, as well as increasing the CEC. 4. In the local cytokine status for acute EBV infection, in contrast to bacterial tonsillitis characterized by increased levels ІNF-Gamma and IL-10. 5. The treatment of acute exacerbations of chronic tonsillitis often empirically prescribers ampicillin and amoxicillin. In the case of EBV infection activation function of these antibiotics is contraindicated and may cause allergic reactions, up to anaphylactic shock.